ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUMDA BPR BANK CIREBON SEBELUM DAN SESUDAH PENGUMUMAN PANDEMI COVID-19 - Siti Nurmeniar Said; Putri Agustina (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
The purpose of this study was to determine the financial performance of Perumda BPR Bank Cirebon before and after the Covid-19 pandemic. The research method used is descriptive comparative using secondary data in the form of financial reports for the period January 2019 to December 2020. The research variable is financial performance with financial ratio indicators, namely Current Ratio, Quick Ratio, Operational Costs and Operational Income (BOPO), Return on Assets (ROA), Return On Equity (ROE), Debt to Assets Ratio (DAR). The results of this study indicate that several indicators of financial performance in Perumda BPR Bank Cirebon have increased and decreased. The highest growth is found in the profitability ratio indicator, namely Return On Equity. This proves that the financial condition of Perumda BPR Cirebon during the pandemic period is quite stable.